STRATEGIES FOR SUCCESSFUL DEVELOPING A SUSTAINABLE BEHAVIOR MANAGEMENT CULTURE AS AN IDENTITY OF QUALITY EDUCATION - Zaini, Akhmad; Gunawan, Zaini; Aliwafa, Aliwafa; Sugiono, Sugiono; Khaer, Abu (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The aim of education is not only to educate students intellectually, but affective and psychomotor values cannot also be ignored, therefore a culture of behavior management is very necessary to form a quality educational identity. This research also proposes a strategic framework that includes the stages of identifying core values, developing supporting policies, developing communication strategies, as well as ongoing implementation and monitoring. The results of this research provide insight into how a culture of sustainable behavior management can shape the identity of quality education. The practical implication is to provide guidance for educational institutions to develop a culture of sustainable behavior management in order to achieve optimal educational quality. This research also underscores the importance of collaboration between stakeholders to create a supportive and sustainable educational environment